Pemertahanan Bahasa sebagai Konstruksi Identitas pada Masyarakat Adat Jalawastu di Brebes Jawa Tengah - Koeshandoyo, Eko Wahyu; Sofianto , Kunto; Sunarya, Budi Gustaman; Septiani , Ayu (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
Studies on indigenous communities have been conducted with various results on cultural elements as their research focus. Language, as one of those elements, is an essential factor in the survival of the traditions and beliefs. This article discusses how the Jalawastu community maintains their indigenous language of Brebes Sundanese dialect in Javanese-speaking culture in Central Java. The novelty of this study was to discover how the traditional community perceived their language, why they needed to maintain it, and what obstacles they had in the process.  This ethnographic research was conducted in Jalawastu Cultural Village in Desa Ciseureuh, Kecamatan Ketanggungan, Kabupaten Brebes between October 2022 and May 2023. Data was collected using in-depth interviews and observation. Those who participated in this study were kuncen, (cultural council chief), pemangku adat (traditional ruler), kepala dusun (the village chief), and  Jalawastu community member. The study revealed that the community attempted to maintain their dialect because they viewed the importance of their language in their daily verbal interaction, both in social activities and rituals, and the need to hold their social identity as Jalawastu village members. The attempt to preserve the use of the language was based on the social belief, that is, to respect their ancestors in order to avoid misfortunes. These efforts were once hindered when the provincial government imposed the language policy to teach only Javanese in elementary schools instead of Sundanese. With Brebes Bupati's regional decrees, they could eventually teach back the language in formal elementary schools.